The Intellect and Religion in Farabi's Philosophy - Mehri Changi Ashtiyani (حکمت معاصر, 2012)
The role of the intellect (or reason) and its functions in religious speculation is very important. In the Islamic context, a wide variety of functions are attributed to the intellect. Most of the philosophical and theological schools as well as the theoretical disputes have their origin in the various status attributed to the intellect and intellection. Kindi, Avicenna, Farabi, Suhrawardi and Mulla Sadra are among the great Islamic philosophers who have postulated various functions for the intellect and speculated on its relationship with religion. Farabi particularly stands out on this topic. Farabi developed his philosophical position while the Islamic word was caught in doctrinal, juridical and theological quandaries and arguments, political differences and social upheavals, and wars between various groups claiming authority. In that period, having lost its religious principle, Islam was in a state of crisis and needed a scientific explanation for its existing challenges. Hence, people were drawn towards Greek philosophy, and its principles were used to solve problems in religious thinking. Hence, we see that Farabi, using Greek philosophy and logical deduction, strive for a better understanding of religion. He considers the general Islamic principles and the law of the revelation, a key guaranteeing happiness in this world and the next. Farabi argues that it is possible for the human intellect to understand these general Islamic principles and laws by comprehending them logically. According to him, the intellect has a universal nature, and accepting its rational proofs is a common and unalterable factual possibility for all human beings. Farabi believes that the teaching of philosophy and religion are the same. They both come from the source of revelation, or emanation of the agent intellect, and both ultimately leads to perfection and happiness. Farabi does not see any tension between religion and rational intellection and attributes a unique status to the intellect. Leaving aside his unconventional position that the philosopher has a higher status than the prophet, Farabi believes that the philosopher talks using the attributes of speech, and relying upon reason, while the prophet convinces and persuades people by means of the agent intellect imprint upon his imaginal faculty.